FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN TOKO HANDPHONE DI KECAMATAN KEDIRI KABUPATEN TABANAN - MARTA, I NYOMAN GEDE; PYNATIH, NGURAH MADE NOVIANHA; ARTINI, NI RAI (GANEC SWARA, 2023)
The role of Small and Medium Enterprises (SMEs) is as the main source of employment and income. In Tabanan Regency, especially in Kediri District, there are relatively small and medium-sized entrepreneurs, one example being mobile phone stores.This research aims to examine the partial and simultaneous effects of working hours, capital, workforce size, and business duration on the income of mobile phone stores in Kediri District, Tabanan Regency.A total of 38 entrepreneurs were sampled using a census technique. Data analysis was conducted using classic assumption tests, including normality test, multicollinearity test, autocorrelation test, and heteroskedasticity test, as well as multiple linear regression analysis.Based on the SPSS calculations, it was found that working hours, capital, workforce size, and business duration have partial effects on the income of mobile phone stores in Kediri District, Tabanan Regency. The estimation results from t-tests and F-tests indicate that working hours, capital, workforce size, and business duration have significant simultaneous effects on the income of mobile phone stores in Kediri District, Tabanan Regency